Toll-Like Receptor 21 of Chicken and Duck Recognize a Broad Array of Immunostimulatory CpG-oligodeoxynucleotide Sequences - Chuang, Yu-Chen (Vaccines (Basel), 2020)
CpG-oligodeoxynucleotides (CpG-ODNs) mimicking the function of microbial CpG-dideoxynucleotides containing DNA (CpG-DNA) are potent immune stimuli. The immunostimulatory activity and the species-specific activities of a CpG-ODN depend on its nucleotide sequence properties, including CpG-hexamer motif types, spacing between motifs, nucleotide sequence, and length. Toll-like receptor (TLR) 9 is the cellular receptor for CpG-ODNs in mammalian species, while TLR21 is the receptor in avian species. Mammalian cells lack TLR21, and avian cells lack TLR9; however, both TLRs are expressed in fish cells. While nucleotide sequence properties required for a CpG-ODN to strongly activate mammalian TLR9 and its species-specific activities to different mammalian TLR9s are better studied, CpG-ODN activation of TLR21 is not yet well investigated. Here we characterized chicken and duck TLR21s and investigated their activation by CpG-ODNs. Chicken and duck TLR21s contain 972 and 976 amino acid residues, respectively, and differ from TLR9s as they do not have an undefined region in their ectodomain. Cell-based TLR21 activation assays were established to investigate TLR21 activation by different CpG-ODNs. Unlike grouper TLR21, which was preferentially activated by CpG-ODN with a GTCGTT hexamer motif, chicken and duck TLR21s do not distinguish among different CpG-hexamer motifs. Additionally, these two poultry TLR21s were activated by CpG-ODNs with lengths ranging from 15 to 31 nucleotides and with different spacing between CpG-hexamer motifs. These suggested that compared to mammalian TLR9 and grouper TLR21, chicken and duck TLR21s have a broad CpG-ODN sequence recognition profile. Thus, they could also recognize a wide array of DNA-associated molecular patterns from microbes. Moreover, CpG-ODNs are being investigated as antimicrobial agents and as vaccine adjuvants for different species. This study revealed that there are more optimized CpG-ODNs that can be used in poultry farming as anti-infection agents compared to CpG-ODN choices available for other species.